2020
DOI: 10.3892/or.2020.7890
|View full text |Cite
|
Sign up to set email alerts
|

TELO2 induced progression of colorectal cancer by binding with RICTOR through mTORC2

Abstract: Colorectal cancer (CRC) is a common cancer worldwide, and its treatment strategies are limited. The underlying mechanism of CRC progression remains to be determined. Telomere maintenance 2 (TELO2) is a mTOR-interacting protein. Both the role and molecular mechanism of TELO2 in cancer progression remain unknown. In this study, the gene expression database of normal and tumor tissue, in addition to western blot analysis, and immunohistochemistry (IHC) were used to determine the expression and location of TELO2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Among the intersected omics features, TELO2 and ZYMND19 are the most significant DEGs. Guo et al [ 21 ] revealed that TELO2 was significantly upregulated in colorectal cancer (CRC), which was concordant with the regulatory pattern in our study. Additionally, the significant restraints of the growth, cell cycle, and metastasis of CRC cells manifest after TELO inhibition, indicating that TELO2 promotes tumor progression.…”
Section: Discussionsupporting
confidence: 92%
“…Among the intersected omics features, TELO2 and ZYMND19 are the most significant DEGs. Guo et al [ 21 ] revealed that TELO2 was significantly upregulated in colorectal cancer (CRC), which was concordant with the regulatory pattern in our study. Additionally, the significant restraints of the growth, cell cycle, and metastasis of CRC cells manifest after TELO inhibition, indicating that TELO2 promotes tumor progression.…”
Section: Discussionsupporting
confidence: 92%
“… 27 Referring to previous research, the cell staining intensity was classified as 4 grades, with 0 points for negative, 1 point for low positive, 2 points for median positive, and 3 points for strong positive. 28 The final results were calculated as the score of the cell staining intensity and its percentage of cells.…”
Section: Methodsmentioning
confidence: 99%
“…The next day, the samples were incubated with biotin-labeled secondary antibody, stained with 3,3ʹ-Diaminobenzidine (DAB) (Agilent Technologies, Santa Clara, CA, USA) and hematoxylin, and finally photographed using a confocal microscopy. Immunohistochemical scoring was performed according to a method detailed in a previous study [ 49 ].…”
Section: Methodsmentioning
confidence: 99%